Locating the Voices of Malaysian Independent Documentary Filmmakers - Candida, Jau Emang; Mahyuddin, Ahmad; Lee, Yuen Beng (School of Social Sciences, USM, 2016)
Since 2000, the advent of digital filmmaking in Malaysia has become the catalyst to the rise of independent documentary filmmakers. This phenomenon has garnered a steady interest amongst young and urban filmmakers led by Amir Muhammad who has released documentaries about Malaysians such as The Big Durian (2004), and The Last Communist (2006), Village People Radio Show (2007). These works, then paved the way for more independent (indie) documentary filmmakers whose works are aligned with the increased concerns about human rights, social and political injustice, environmental issues as well as displaced community. Despite their efforts, there still remains a lacking in terms of acceptance by local cinemas or TV stations towards the documentaries by such independent filmmakers. Nevertheless, their presence continues to stir a steady debate as to where these talented documentary filmmakers are headed to in the context of social activism and social engagement that seem to rise significantly among the urbanites. This too, led to the discussion on public discourse about how documentaries are capable of providing spaces for discussion and engagement. This article, therefore, maps the works of selected documentary filmmakers while discussing how their works emerge as a site for negotiating human rights, social and political issues in Malaysia today.